A review on research development of SiC trench gate MOSFET technology - LUO Haihui; LI Chengzhan; YAO Yao; YANG Songlin (机车电传动)
The third-generation wide-bandgap semiconductor silicon carbide (SiC) MOSFET devices have rapidly become a research hotspot in the production and research sectors due to their advantages, such as high voltage resistance, high-temperature resistance and low loss. This paper, in conjunction with the development history of SiC MOSFET devices, discussed the necessity of transitioning from planar gate technology to trench gate technology. It elaborated on the technical challenges and research progress related to SiC trench gate MOSFET structure design, trench etching processes, trench gate oxide processes and other core issues. Finally, it provided an outlook for future advanced SiC trench gate MOSFET technology.